Law and social justice : some theories of law in relation to social justice - Goswami, B.; Chaturvedi, Ram Gopal , 1931- (Jaipur : Raj Publishing House, 2007)
In Indian context
1. The theory of law -- 2. Social justice
Includes bibliographical references and index
Keywords: Social justice -- India; Sociological jurisprudence